Mapping the future: bibliometric insights into ferroptosis and diabetic nephropathy - Wei, Tangwen; Qin, Yang; Lin, Xiaohui; Wang, Xiujuan; Chen, Suyi; Chen, Xia; Yan, Nan; Wei, Xinyi; Zhang, Zhichang; Wei, Bing (Frontiers in Physiology, 2025)
BackgroundDiabetic nephropathy (DN), a leading cause of end-stage renal disease, exerts a substantial burden on healthcare systems globally. Emerging evidence highlights ferroptosis - an iron-dependent form of cell death driven by lipid peroxidation and glutathione depletion - as a critical contributor to DN progression via oxidative stress, tubular injury, and glomerular dysfunction. Despite increasing research interest, a comprehensive synthesis of research trends and mechanistic insights is lacking.ObjectiveThis study integrated bibliometric analysis with a mechanistic review to map the evolving ferroptosis landscape in DN, identify research hotspots, and propose future directions for therapeutic development.MethodsIn total, 86 publications (2018–2023) were retrieved from the Web of Science Core Collection and analyzed using CiteSpace and VOSviewer. Co-occurrence networks, citation trends, and keyword bursts were examined to delineate global contributions, collaborative networks, and emerging themes.ResultsAnnual publication numbers surged 12-fold after 2020, with China contributing the highest proportion (60.4%), and led by institutions such as Zhengzhou University. The United States of America and Germany showed high centrality in collaborative networks. Key research themes included glutathione peroxidase 4 (GPX4)-mediated antioxidant defenses, acyl-CoA synthetase long-chain family member 4 (ACSL4)-mediated lipid remodeling, and iron dysregulation. Frontiers in Endocrinology (nine articles) and Free Radical Biology and Medicine (highest citation count: 171) emerged as pivotal publication platforms. Mechanistic analyses identified three ferroptosis defense axes (GPX4, FSP1/CoQ10, and GCH1/BH4) and cell type-specific vulnerabilities in tubular, podocyte, and endothelial cells. Preclinical agents, including ginkgolide B (GB) and dapagliflozin, effectively restored iron homeostasis and attenuated oxidative damage.ConclusionFerroptosis is a promising therapeutic target for DN, yet its clinical translation remains in its infancy. Future efforts should prioritize large-scale clinical trials, single-cell mechanistic profiling, and interdisciplinary integration to bridge molecular insights with precision therapies. This study provides a roadmap for advancing ferroptosis-targeted interventions for DN, emphasizing global collaborations and biomarker-driven strategies.